Insights into chemical reactions of graphitic carbon nitride with alkali halides - Kouki Akaike; Ayako Hosokai; Kazuki Tajima; Haruhisa Akiyama; Hiroki Nagashima (JPhys Energy, 2022)
The calcination of nitrogen-rich molecules, such as melamine and urea, with inorganic salts, results in chemical modifications of graphitic carbon nitride (g-CN), a polymeric photocatalyst driven by visible-light illumination. Alkali halides are abundant and low-cost additives for that purpose and enhance photocatalytic activity. The precursors or condensed carbon nitride polymer react with the salts, even below their melting point; however, the mechanistic understanding of the reaction of g-CN with alkali halides is still unknown. In this study, we investigated reactions of melon, a linear polymer of heptazine monomers, with NaCl, employing Fourier-transform infrared (IR) spectroscopy in solid and gas phases, solid-state nuclear magnetic resonance spectroscopy, temperature-programmed desorption mass spectrometry (TPD-MS), and thermogravimetry. The reaction of melon with NaCl at 500 °C substitutes a fraction of amino groups with cyanamide moiety and deprotonates NH groups bridging heptazine monomers. The formation of NH _4 Cl during the calcination implied that NaCl reacted with NH _3 that had evolved as a result of the condensation of melon molecules. TPD-MS and gas-phase IR confirmed the presence of NH _3 as well as H _2 O and CO _2 above 400 °C. These gaseous molecules and NaCl lead to NaHCO _3 via the Solvay process reactions. NaHCO _3 is decomposed into Na _2 CO _3 at the calcination temperature. The base and gaseous H _2 O finally cause OH ^− . The resultant hydroxyl anion introduces cyanamide groups into the melon, deprotonates the NH groups, and decomposes a fraction of the polymer into isocyanic acid via the formation of sodium cyamelurate as an intermediate. The reaction mechanisms proposed in this study will promote the molecular understanding of the roles of additives in the modification of the chemical structure of g-CN photocatalysts.